Dental treatment in patients with hereditary coagulopathy: hemophilia and Von Willebrand's disease (Research, Society and Development, 2023)
Coagulopathy is defined as a “bleeding disease”, resulting from the quantitative and/or qualitative deficiency of one or more plasma proteins (coagulation factors). The common characteristic of hereditary coagulopathies is the reduction in the formation of thrombin, an essential factor for blood clotting. In this sense, this research has the objective of carrying out a literature review about the dental procedures that can be routinely performed in patients with hereditary coagulopathy. For the construction of this work, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. Bleeding disorders have been of great concern to healthcare professionals, including dentists, for some time. Hemophilia is the most common bleeding disorder, affecting 1 in 10,000 people worldwide. Oral health is often neglected by hemophiliacs for fear of bleeding during procedures, and the wealthy population is no exception. Early dental care is of paramount importance in these patients to avoid invasive procedures in the future. A thorough understanding of the problems, especially hemophilia, helps the dentist to carry out a systematic assessment and anticipate potential dangers, rather than being caught off guard with sparse and desperate local hemostatic measures.